Local Honeybee Post-harvest and Marketing Challenges in Bongkasa Pertiwi Village, Bali, Indonesia - Almoneda , Jeremy John L.; Dimabayao , Marc Paul P.; Federis , Jannica Elaine; Flora , Antonette M.; Araujo, Cairos Do Carmo; Satriya, Aryan; Hidalgo, Hanilyn A.; Amerta, I Made Suniastha; Mangku, I Gede Pasek; Sanjaya, I Gusti Agus Maha Putra; Situmeang, Yohanes Parlindungan; Purba, Rusta Malum; Utama, Putu Darma (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2025)
Sarining Trigona Pertiwi, a beekeeping group established on June 6, 2020, in Bongkasa Pertiwi Village, Badung Regency, Bali, emerged during the COVID-19 pandemic to provide supplementary income amidst economic turmoil. Starting with 470 colonies of stingless bees, including Tetragonula Laevicheps and Heterotrigona Itama, the organization has expanded to 620 colonies and now consists of 22 members. With financial backing from The Aqua, a private company, the group produces honey in 250 ml and 100 ml sizes and has embraced eco-tourism to educate visitors about honey harvesting and environmental conservation. Despite employing best practices such as regular hive inspections and sustainable harvesting methods, Sarining Trigona Pertiwi faces substantial postharvest and marketing challenges. These include a lack of standardized postharvest protocols, inadequate hygiene and storage practices, high moisture content in honey, and the absence of commercial licenses. Marketing obstacles encompass an undefined market, poor packaging and labeling, limited social media presence, and ambiguous brand identity. Addressing these issues is critical for enhancing Sarining Trigona Pertiwi's operations' productivity and sustainability, ensuring this community initiative's long-term success and economic stability. Contribution to Sustainable Development Goals (SDGs)SDG 1: No PovertySDG 2: Zero HungerSDG 8: Decent Work and Economic GrowthSDG 12: Responsible Consumption and Production